2012
DOI: 10.5713/ajas.2012.12404
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic Effect of Pifithrin-α on Preimplantation Porcine In vitro Fertilized Embryo Development

Abstract: The aim of this study was to investigate the impact of a reported p53 inhibitor, pifithrin-α (PFT-α), on preimplantation porcine in vitro fertilized (IVF) embryo development in culture. Treatment of PFT-α was administered at both early (0 to 48 hpi), and later stages (48 to 168 hpi) of preimplantation development, and its impact upon the expression of five genes related to apoptosis (p53, bak, bcl-xL, p66Shc and caspase3), was assessed in resulting d 7 blastocysts, using real-time quantitative PCR. Total cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(60 reference statements)
0
2
1
Order By: Relevance
“…Therefore, in this study, TERTtransfected MSCs may have improved DNA stability and reduced apoptosis from replicative senescence. However, this study was not consistent with a previous study that showed an increased apoptosis causes a decrease in the total cell number during the blastocyst stage Mulligan et al, 2012). This is probably due to the dynamic changes in the pattern of expression of genes according to the embryo development stages or the time gap of gene expression and cellular functions in the embryos (Kumar et al, 2012;Gouveia et al, 2020).…”
Section: Gene Expression Analysis During the Blastocyst Stagecontrasting
confidence: 99%
“…Therefore, in this study, TERTtransfected MSCs may have improved DNA stability and reduced apoptosis from replicative senescence. However, this study was not consistent with a previous study that showed an increased apoptosis causes a decrease in the total cell number during the blastocyst stage Mulligan et al, 2012). This is probably due to the dynamic changes in the pattern of expression of genes according to the embryo development stages or the time gap of gene expression and cellular functions in the embryos (Kumar et al, 2012;Gouveia et al, 2020).…”
Section: Gene Expression Analysis During the Blastocyst Stagecontrasting
confidence: 99%
“…The RT-qPCR reactions were run with with Stratagene Mx3000P (Agilent Technologies, Santa Clara, CA, USA) real-time PCR equipment. The primers used in this study and their annealing tempertures were selected from the reference literature: Bax—sense 5′ GCT GAC GGC AAC TTCA ACT G 3′ and antisense 5′CCG ATC TCG AAG GAA GTC CA3′; Bcl2—sense 5′GGG ACG TCA GGT CAC TGA AT 3′ and antisense 5′ GAA ACC CCT AGT GCC ATC AA 3′; Reference gene β-actin—sense 5′ GTG ATC TCC TTC TGC ATC CTG TC 3′ and antisense 5′ CTC GAT ATG AAG TGC GAC G 3′ [ 40 ]; P53—sense 5′ GCA ATG GAT GAG GCG CAG TC 3′ and antisense 5′ TGG CAC TCT GGA GGC GTC AT 3′ [ 37 ]; and Ptx 3—sense 5′ TCA GGA ACA ATG TGA CCC GT 3′ and antisense 5′ TCA GCT ATC AGT CCA CTG GC 3′ [ 37 ]. The primers sequences were synthesized by Eurogentec (Amsterdam, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…The p53 gene and the p53 protein family is responsible for the genomic integrity of the germline [ 36 ]. In oocyte maturation, the p53 gene has been found to activate in response to stressors and therefore is an ideal marker for quantifying the viability of oocytes and embryos [ 37 ]. Ptx3 is a protein that ensures the formation, organization and stability of the extracellular cumulus matrix, through the mediation of the production and architecture of hyaluronan polysaccharides, secreted by cumulus cells [ 38 ].…”
Section: Introductionmentioning
confidence: 99%